Application of Sustainable Agricultural Technology to Increase Productivity and Food Security - Harun Rasyid; Gumoyo Mumpuni Ningsih (Journal of World Science, 2024)
Food security is an important global issue to overcome. The increasing world population and climate change bring new challenges to ensuring the availability of sufficient and nutritious Food. Sustainable agriculture offers solutions to increase productivity and Food security while preserving the environment. This research aims to evaluate the effectiveness and impact of implementing sustainable agricultural technology in increasing agricultural productivity and food security in an area or community. This study used qualitative research methods. The data collection technique in this research is a literature study. The data that has been collected is then analyzed in three stages, namely data reduction, data presentation, and conclusion. The research results show that sustainable agricultural technology can increase productivity and Food security. Farmers who apply sustainable agricultural technology generally produce higher yields and are more resistant to pests and disease. However, its implementation still needs challenges, such as limited access to technology and knowledge, high costs, and lack of policy support.